Effects of value and interest intervention on EFL student teachers’ research motivation in the Chinese context - Bi, Peng; Liu, Honggang (Frontiers in Psychology, 2022)
Language teacher research is conducive to the development of teachers’ teaching skills and professional career. Thus, in many English teacher education programs, student teachers are required to do research. However, some empirical findings have suggested that EFL student teachers lack research motivation. Finding suitable interventions to increase their research motivation has become increasingly necessary. In light of the importance of research motivation intervention, this study designed an experiment to testify the effect of value and interest intervention, during which positive research experiences were shared to improve student teachers’ research motivation. Quantitative questionnaires and semi-structured interviews were used to gather evidence on student teachers’ research motivation. The interview data revealed that students’ research motivation was influenced by their belief about the value of research in terms of their teaching practice. The experiment results suggested that student teachers’ intrinsic and extrinsic research motivations both increased after the intervention. However, this intervention was not effective in curbing their failure avoidance tendency. Pedagogical implications of the results are also discussed at the end of this article.